Labor law reforms and labor market performance in Egypt - Ahmed Fayez Abdelgouad (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
This study introduces a review of the institutional framework in the Egyptian labor market to show how it is regulated by discussing extensively the most recent labor law regulations in Egypt and the main reasons behind enacting this law. The paper guides also to different data sources that can be used and highlights a number of empirical studies about the labor market in Egypt. Finally, it concludes that further reforms are still required to improve labor market efficiency in Egypt.
Keywords: J31; J41; J51; 330; labor law; reforms; labor market flexibility; Egypt